A BP3-AlP3 heterobilayer for the bifunctional photocatalysis of CO2 reduction - Zewdie, Getasew Mulualem; Kim, Ju Yeon; Kang, Hong Seok (Applied surface science, 2023)
A van der Waals heterobilayer of γ-BP3 and δ-AlP3 monolayers is proposed for a bifunctional photocatalysis of CO2 to CO on its two sides, based on many-body GW-BSE and Gibbs free energy calculations. [Display omitted] •Using first-principles calculations, we propose γ-BP3 monolayer and homobilayer.•We also propose a heterobilayer of γ-BP3 and δ-AlP3.•The heterobilayer displays a direct gap of 1.46 eV from the GW calculation.•The heterobilayer does not show any noticeable excitonic binding from the BSE.•The heterobilayer is promising for bifunctional photocatalysis of CO2 reduction. Using first-principles calculations, we propose γ-BP3 monolayer (ML) and its homobilayer not reported thus far. A heterobilayer (HtBL) composed of the γ-BP3 and δ-AlP3 MLs is also proposed, which displays a direct gap of 1.46 eV in the context of the many-body G0W0 method. The G0W0 band offset of the band edge positions with respect to the Fermi levels of a pair of half-reactions (HRs) for CO2 reduction reaction (CO2RR) satisfies thermodynamic criteria for its reduction to CO at pH = 0. The Gibbs free energy calculation on the BP3 side shows that the HtBL should be very efficient for the corresponding reduction HR (RedHR) in that no overpotential is required. On the AlP3 side, another Gibbs free energy calculation for the corresponding oxidation HR (OxHR) indicates that our HtBL is subject to an overpotential of 1.27 eV. However, it should be quite advantageous for the OxHR, because a solution of the Bethe-Salpeter equation shows no noticeable exciton binding due to carrier separation. The HtBL comprises the first example of the bifunctional catalysis for the CO2RR based on an atomically thin 2D material. Compared to bulk heterojunction, one of its great advantages could be a substantial reduction in power consumption.